Thermal fatigue analysis on cracked plenum barrier plate of open-cycle gas turbine frame - Rashid A.Z.; Purbolaksono J.; Ahmad A.; Ahmad S.A. (2023)
Failure investigation is carried out following repeating findings of several obvious surface-crack spots on the weld joint zone of a plenum barrier plate of open-cycle gas turbine frame. The exhausted hot compressed air will flow through the cracks entering the load compartment which contains temperature sensitive instrumentations and shaft bearings. The modified model of the barrier plate is presented for redesign consideration. Visual inspection, microscopic examination on the cracked barrier plate and thermal fatigue analyses based on strain-life approach are carried out. The life expectancies of the original and modified models for the barrier plate design are evaluated. The finding indicates that the modified model could withstand against the thermal fatigue longer than that of the original model. 2009 Elsevier Ltd. All rights reserved.